Microinsurance Decisions: Gendered Evidence from Rural Bangladesh. (1st January 2016) - Clarke, Daniel J.; Kumar, Neha
Abstract: Most index-based insurance products have been developed without giving explicit attention to gender. However, there is ample of evidence that shocks affect men and women differently and that they allocate resources in different ways. In Bangladesh, it is often assumed that women are less involved in agriculture, and, therefore, agricultural insurance might not be of interest to rural women. However, this assumption has not been tested in the field. This article draws from a field research experiment to examine the gendered aspects of willingness to pay for index-based insurance in Bangladesh. Participants were presented with risky lotteries and a specific insurance contract and were asked to choose how much, if any, of the insurance they wanted to buy at a given price. The probability structure, whether the risk was catastrophic or moderate and whether there was high or low basis risk, varied within sessions. The price of the insurance varied across sessions. Each participant was also given a short questionnaire, which collected information on the demographic characteristics, risk preferences, agricultural risks, knowledge of insurance products, and asset ownership. In the study, 97 percent of the participants decided to buy agricultural insurance, with no significant differences between men and women, even though women were less involved in agricultural decision-making. We found a small decrease in take-up for the low-probability event, driven by the women in the sample. When we examined the number of units bought, we found that men were likely to buy more units than women. Total wealth, as captured by total land owned, had no effect on the units bought. However, among women, total wealth mattered and had a positive correlation. Finally, we found that women had less education and lower financial literacy than their male counterparts, and did not have the experience possessed by men to understand agricultural risks. It placed them at a disadvantage when making insurance purchase decisions.